2002
DOI: 10.1152/ajprenal.00007.2002
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β and CTGF have overlapping and distinct fibrogenic effects on human renal cells

Abstract: Transforming growth factor-beta (TGF-beta) and connective tissue growth factor (CTGF) are ubiquitously expressed in various forms of tissue fibrosis, including fibrotic diseases of the kidney. To clarify the common and divergent roles of these growth factors in the cells responsible for pathological extracellular matrix (ECM) deposition in renal fibrosis, the effects of TGF-beta and CTGF on ECM expression in primary human mesangial (HMCs) and human proximal tubule epithelial cells (HTECs) were studied. Both TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 69 publications
4
118
0
2
Order By: Relevance
“…mainly transduces myofibrotic activation to tubular epithelial cells (Gore-Hyer et al, 2002;Lin et al, 2005). Our study demonstrated that honokiol attenuated TGF-b1 induction in the UUO kidneys and also reduced CTGF expression in NRK-52E cell lines and in kidneys of UUO-treated rats.…”
Section: Figuresupporting
confidence: 50%
“…mainly transduces myofibrotic activation to tubular epithelial cells (Gore-Hyer et al, 2002;Lin et al, 2005). Our study demonstrated that honokiol attenuated TGF-b1 induction in the UUO kidneys and also reduced CTGF expression in NRK-52E cell lines and in kidneys of UUO-treated rats.…”
Section: Figuresupporting
confidence: 50%
“…TGF-β has been clearly implicated in the pathogenesis of one microvascular complication, diabetic nephropathy, and has been shown to promote renal cell hypertrophy and stimulate formation of extra cellular matrix in the kidney (Ohashi et al, 2004); Gore-Hyer et al, 2002;Kim et al, 2001;Park et al, 1997;Sharma et al, 1997). It also has been shown that overeexpression of TGF-β in diabetic rat glomeruli promotes extra cellular matrix accumulation that is responsible for glomerular injury, and treatment with anti-TGF-β antibody ameliorates diabetic nephropathy (Hill et al, 2001;Ma et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that overeexpression of TGF-β in diabetic rat glomeruli promotes extra cellular matrix accumulation that is responsible for glomerular injury, and treatment with anti-TGF-β antibody ameliorates diabetic nephropathy (Hill et al, 2001;Ma et al, 2004). In previous tissue culture and animal studies, cellular matrix production was stimulated by high glucose levels, was associated with increased TGF-β expression, and the matrix stimulatory effects of high glucose were prevented by anti-TGF-β therapy (Gore-Hyer et al, 2002;Kim et al, 2001;Ohashi et al, 2004;Park et al, 1997;Sharma et al, 1997). Despite a strong association of TGF-β with renal disease no association with neuropathy has so far been established.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the same study shows that TGF-β directly induces transformation of mesangial cells into myofibroblasts without interference by CTGF. Other studies demonstrated that TGF-β and CTGF both induced collagen protein expression in cultured human mesangial cells, whereas only TGF-β was able to induce collagen protein expression in human proximal tubular cells [72]. Furthermore, both growth factors were capable of inducing tenascin-C, a marker for epithelial-mesenchymal transdifferentiation, in proximal tubular cells.…”
Section: Connective Tissue Growth Factormentioning
confidence: 95%